Water Can Protect the Earth and People - A Comparison of Two Storage Energy Reactions - Jin , Jia-Min; Bao, Wei-Feng (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 2, 2023)
Two storage energy reactions, namely, carbon gasification C+CO2=2CO and carbon water gasification C+H2O=H2+CO reactions were compared. The results show that the carbon water gasification reaction has many advantages, such as: higher caloric value of gas, high storage energy index, faster reaction speed, abundant resources, low price, low production cost, significant emission reduction, environmental protection. Convenient for rural promotion. Water naturally can protect the earth and human beings.